Method for optimizing performance of QLED device
By supercritical carbon dioxide treatment on QLED devices, it affects its zinc oxide layer to weaken the electron transport capability, solving the problems of electron and hole injection imbalance and fluorescence quenching in QLED devices, and improving the efficiency and life of the device.
Patent Information
- Application Number
- CN202411771050.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-21
AI Technical Summary
Existing QLED devices have problems with quantum dot fluorescence quenching caused by electron and hole injection imbalance, low efficiency and ZnO surface defect state, and inert interpolation and cation-doped ZnO have limited improvements in device performance.
By placing the packaged QLED device in a supercritical reactor, using a combined treatment of supercritical carbon dioxide or supercritical carbon dioxide and trace amounts of water, the pressure and temperature are controlled for supercritical treatment, affecting the zinc oxide layer to reduce electron transport capacity and balance carrier injection.
It improves the external quantum efficiency of QLED devices, extends its service life, and effectively reduces the fluorescence quenching caused by contact between the electron transport layer and the luminescent layer.
Smart Images

Figure CN119677364A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of optoelectronic materials technology, and specifically relates to a method for optimizing the performance of QLED devices. Background Art
[0002] With in-depth research on QDs materials and continuous optimization of device structures, QLED devices have made significant progress in performance. Due to their superior performance and broad application prospects, QLED is considered a strong candidate for next-generation display technology.
[0003] Through in-depth research, scientists generally believe that the existing problems in QLED devices are mainly caused by excessive electron injection, including an imbalance between electron and hole injection, low efficiency, and quantum dot fluorescence quenching caused by abundant surface defect states in ZnO. Although adding inert intercalation layers and cation-doped ZnO as an electron transport layer has improved the performance of QLED devices, the following problems still exist:
[0004] One approach involves inserting an inert layer between the QD / ZnO layer. Some researchers have used a method of inserting polymethyl methacrylate (PMMA) between the electron transport layer (EML) and the hole transport layer (ETL), adding one layer of material and two interfaces. This makes the device structure more complex and brings new challenges to the device fabrication process and theoretical research.
[0005] Secondly, at high voltages, the effect of cation doping on ETL electron transport efficiency remains limited. Some researchers have used Al... 3+ Doped zinc oxide nanoparticles (ZnO NPs) are used as the electron transport layer in QLEDs to replace ZnO NPs. However, cation doping of ZnO does not significantly improve the efficiency roll-off problem of QLED devices, and the synthesis and purification of modified ZnO are more difficult, which is not conducive to its commercialization.
[0006] Invention patent CN113437187A discloses a supercritical processing method that repairs crystal defects in the semiconductor structure of a light-emitting diode (LED) using elements of a second substance in a supercritical state, thereby improving the semiconductor's optical performance. However, this method primarily processes simple microcontrollers (potassium nitride) and does not address the processing of more complex, defect-ridden, and well-packaged QLED devices. Therefore, there is an urgent need for an effective method to optimize the optical performance of QLED devices. Summary of the Invention
[0007] To address the aforementioned problems, one objective of this invention is to provide a method for optimizing the performance of QLED devices. After supercritical treatment, the conduction band energy level position of the electron transport layer material is slightly increased, and surface defect states are suppressed. Consequently, its electron transport capability is somewhat weakened, and the overall resistance of the device is slightly increased. This improves the imbalance of positive load carrier injection, thereby increasing the efficiency of the QLED device and extending its lifespan.
[0008] To achieve the above objectives, the present invention adopts the following technical solution:
[0009] A method for optimizing the performance of QLED devices includes the following steps: placing the packaged QLED device in a supercritical reactor, introducing carbon dioxide into the reactor, controlling the pressure and temperature inside the reactor, and performing supercritical treatment;
[0010] Alternatively, the packaged QLED device can be placed in a supercritical reactor, water can be added to the reactor, and then carbon dioxide can be introduced into the reactor to control the pressure and temperature inside the reactor for supercritical treatment.
[0011] When QLED devices are treated with supercritical carbon dioxide, the supercritical CO2, due to its strong diffusivity, can reach the zinc oxide layer. This invention experimentally demonstrates that this process has almost no effect on the quantum dot layer. Furthermore, considering that the cathode of the device is composed of metallic Al and is deposited onto the device via vapor deposition, its structure itself does not contain small organic molecules, making it difficult for supercritical fluids to modify it. Therefore, the supercritical treatment of this invention only affects the zinc oxide layer of the device.
[0012] Furthermore, due to its strong solubility and the fact that impurity molecules in zinc oxide films are typically small, the inventors hypothesize that supercritical carbon dioxide not only effectively removes these impurities but also suppresses defect states on the ZnO surface to some extent, thereby reducing electron transport capability and helping to balance carrier injection, thus improving the overall performance of the device.
[0013] Furthermore, after the QLED device undergoes combined treatment with supercritical CO2 and a suitable amount of water, the supercritical CO2, due to its strong solubility, can dissolve trace amounts of water and, utilizing its excellent diffusivity, can carry these trace amounts of water to the zinc oxide layer. Similarly, experimental data from this invention confirms that the effect of this process on the quantum dot layer is almost negligible. The Al cathode, being free of small organic molecules and formed through vapor deposition, exhibits strong resistance to the modification effects of supercritical fluids; therefore, the inventors believe that the influence of water is mainly concentrated in the zinc oxide layer. Thus, it is speculated that moisture may further improve device performance by passivating surface defects in the zinc oxide. After the treatment, the supercritical CO2 may also remove previously present impurities, unreacted solvents, and other organic compound impurities, further suppressing electron transport capability and balancing carrier injection, thereby enhancing device performance.
[0014] Furthermore, the temperature is 40°C to 70°C, the pressure is 1000 psi to 1600 psi, and the supercritical treatment time is 20 min to 60 min.
[0015] Furthermore, the temperature is 50°C to 60°C, the pressure is 1300 psi to 1500 psi, and the supercritical treatment time is 40 min to 50 min.
[0016] Furthermore, the amount of water added is 200–600 μL.
[0017] Furthermore, the amount of water added is 300–600 μL.
[0018] Furthermore, after the supercritical treatment is completed, the carbon dioxide in the reactor is gradually cooled and depressurized to return to the gaseous state, and the treated QLED device is then removed.
[0019] Furthermore, the QLED device, from bottom to top, consists of an anode / hole injection layer / hole transport layer / light-emitting layer / electron transport layer / cathode; the electron transport layer is made of ZnO nanomaterials.
[0020] Compared with the prior art, the beneficial effects of this invention are as follows:
[0021] (1) This invention is the first to use supercritical fluid to process the packaged QLED device, and the experiment proved that supercritical processing can reach the electron transport layer of ZnO-based nanomaterials and hardly affect the quantum dot layer, which can greatly protect the stability of quantum dots.
[0022] (2) The QLED device provided by this invention, after supercritical treatment, does not exhibit significant changes in surface roughness, crystal structure, and energy level structure, but the film thickness is slightly reduced, and the concentrations of oxygen vacancies and hydroxyl oxygen on its surface are decreased. Supercritical carbon dioxide treatment or combined treatment with supercritical carbon dioxide and trace amounts of water passivates the surface defects of zinc oxide. After treatment, supercritical carbon dioxide may also remove previous impurities, unreacted solvents, and other organic compound impurities, further suppressing electron transport capability and thus balancing carrier injection, thereby improving device performance. Therefore, QLED devices packaged through supercritical treatment can effectively reduce fluorescence quenching caused by contact between the electron transport layer and the light-emitting layer, regulate electron injection balance, thereby improving the external quantum efficiency of the QLED device and increasing its operating life. Attached Figure Description
[0023] Figure 1 A schematic diagram of the QLED device structure provided by the present invention;
[0024] Figure 2 XRD patterns of nanomaterial samples provided in Examples 1-2 and Comparative Example 1 of this invention;
[0025] Figure 3 (αhν) is the nanomaterial sample provided in Examples 1-2 and Comparative Example 1 of this invention. 2 -hν curve spectrum;
[0026] Figure 4 Normalized fluorescence spectra of nanomaterial samples provided in Examples 1-2 and Comparative Example 1 of this invention;
[0027] Figure 5 The AFM image of the nanomaterial sample provided in Comparative Example 1 of this invention;
[0028] Figure 6 The AFM image of the nanomaterial sample provided in Example 1 of this invention;
[0029] Figure 7 The AFM image of the nanomaterial sample provided in Example 2 of this invention;
[0030] Figure 8 The C-AFM image of the nanomaterial sample provided in Comparative Example 1 of this invention;
[0031] Figure 9 C-AFM image of the nanomaterial sample provided in Example 1 of this invention;
[0032] Figure 10 C-AFM image of the nanomaterial sample provided in Example 2 of this invention;
[0033] Figure 11XPS image of the nanomaterial sample provided in Comparative Example 1 of this invention;
[0034] Figure 12 XPS image of the nanomaterial sample provided in Example 1 of this invention;
[0035] Figure 13 XPS image of the nanomaterial sample provided in Example 2 of this invention;
[0036] Figure 14 The UPS spectra (secondary electron cutoff edge) of the samples from Examples 1-2 and Comparative Example 1 of this invention are shown.
[0037] Figure 15 UPS spectra of the samples provided in Examples 1-2 and Comparative Example 1 of this invention (Fermi level edge);
[0038] Figure 16 JV characteristic curves of the samples provided in Examples 1-2 and Comparative Example 1 of the present invention;
[0039] Figure 17 Steady-state fluorescence spectra of the samples provided in Examples 1-2 and Comparative Example 1 of this invention;
[0040] Figure 18 Transient fluorescence spectra of the samples provided in Examples 1-2 and Comparative Example 1 of this invention;
[0041] Figure 19 The current density-voltage-brightness curves of the samples provided in Examples 1-2 and Comparative Example 1 of this invention;
[0042] Figure 20 Brightness-external quantum efficiency curves of the samples provided in Examples 1-2 and Comparative Example 1 of this invention;
[0043] Figure 21 The lifetime decay curves of the samples provided in Examples 1-2 and Comparative Example 1 of this invention. DETAILED DESCRIPTION
[0044] The technical solution of the present invention will be further explained below with reference to specific embodiments, comparative examples, experimental examples and accompanying drawings.
[0045] Unless otherwise specified, the raw materials and preparation methods used in the following examples, comparative examples, and experimental cases are all conventional materials and techniques in the art.
[0046] The electron transport layer of the QLED devices in this invention is made of ZnO-based nanomaterials. The preparation method of these ZnO-based nanomaterials is as follows: A 0.1M zinc acetate dimethyl sulfoxide solution is taken, and at room temperature, ZnO is added... 2+ With OH in tetramethylammonium hydroxide -The zinc acetate solution was added to a 0.55M tetramethylammonium hydroxide ethanol solution at a molar ratio of 3:5, and the reaction was carried out at 20°C for 1 hour. Anhydrous ethanol / n-heptane mixed solvent at a mass ratio of 10:90 was added to the reaction solution, and the mixture was centrifuged to obtain ZnO nanomaterials.
[0047] A schematic diagram of the QLED device of this invention is shown below. Figure 1 As shown, the QLED device can be fabricated using methods well-known to those skilled in the art, without any special requirements. In this invention, the preferred method for fabricating the QLED device includes the following steps: sequentially spin-coating a hole injection layer, a hole transport layer, a light-emitting layer, an electron transport layer material, and a metal cathode onto the anode surface to obtain a composite substrate.
[0048] The spin-coating operations for the hole injection layer, hole transport layer, light-emitting layer, and electron transport layer materials, as well as the cathode deposition operations, can be performed using methods well-known to those skilled in the art for fabricating QLED devices, without any special limitations.
[0049] The materials and average thicknesses of the anode, hole injection layer, hole transport layer, light-emitting layer, and cathode described in this invention are all materials and average thicknesses well known to those skilled in the art, and there are no special limitations.
[0050] Example 1
[0051] A method for optimizing the performance of QLED devices includes the following steps:
[0052] (1) Fabrication of QLED devices
[0053] The structure of the QLED device in this embodiment is glass / ITO / PEDOT:PSS / TFB / QDs / ZnO / Al encapsulant cover glass sheet. In order to successfully construct this device structure, the specific processes of cleaning, spin coating, vapor deposition and encapsulation were followed.
[0054] (2) Supercritical processing of QLED devices:
[0055] The packaged QLED device was placed in a supercritical reactor, CO2 was introduced, and the pressure was set to 1200 psi and the temperature to 50°C for 50 minutes to bring the carbon dioxide to a supercritical state. After treatment, the carbon dioxide in the reactor was gradually cooled and depressurized to return to a gaseous state, and then the treated QLED device was removed.
[0056] Example 2
[0057] (1) Fabricate QLED devices, the specific operation is the same as in Example 1;
[0058] (2) Supercritical processing of QLED devices
[0059] The packaged QLED device was placed in a supercritical reactor, and 400 μL of ultrapure water was added. Then, CO2 was introduced, and the pressure was set to 1200 psi and the temperature to 50 °C. The treatment was carried out for 50 minutes to bring the carbon dioxide to a supercritical state. After the treatment was completed, the carbon dioxide in the reactor was gradually cooled and depressurized to return to the gaseous state. The treated QLED device was then removed.
[0060] Example 3
[0061] (1) Fabricate QLED devices, the specific operation is the same as in Example 1;
[0062] (2) Supercritical processing of QLED devices
[0063] The packaged QLED device was placed in a supercritical reactor, and 200 μL of ultrapure water was added. Then, CO2 was introduced, and the pressure was set to 1000 psi and the temperature to 40 °C for 20 minutes to allow the carbon dioxide to reach a supercritical state. After treatment, the carbon dioxide in the reactor was gradually cooled and depressurized to return to a gaseous state, and then the treated QLED device was removed.
[0064] Example 4
[0065] (1) Fabricate QLED devices, the specific operation is the same as in Example 1;
[0066] (2) Supercritical processing of QLED devices
[0067] The packaged QLED device was placed in a supercritical reactor, and 600 μL of ultrapure water was added. CO2 was then introduced, and the pressure was set to 1600 psi and the temperature to 70 °C for 60 minutes to bring the carbon dioxide to a supercritical state. After treatment, the carbon dioxide in the reactor was gradually cooled and depressurized to return to a gaseous state. The treated QLED device was then removed.
[0068] Comparative Example 1
[0069] The difference between Comparative Example 1 and Example 1 is that the QLED device in Comparative Example 1 is not subjected to the supercritical treatment in step (2) after it is prepared.
[0070] Experimental Example 1
[0071] XRD analysis was performed on the supercritical ZnO nanomaterials of Comparative Example 1 and Examples 1-2, and the XRD patterns were obtained as follows: Figure 2 As shown.
[0072] Depend on Figure 2 It can be clearly seen that the diffraction peaks of the three are almost in the same position, which indicates that the supercritical process did not significantly change the crystal structure of zinc oxide.
[0073] Experimental Example 2
[0074] The supercritical ZnO nanomaterials of Comparative Example 1 and Examples 1-2 were subjected to UV-Vis detection, and then the (αhν)2-hν curves were calculated. The results are as follows. Figure 3 As shown; the normalized fluorescence spectrum is as follows Figure 4 As shown.
[0075] exist Figure 3 Within the range of 3.3 to 3.7 eV, the band gap sizes of the nanomaterial samples provided in Examples 1-2 and Comparative Example 1 of this invention were determined. The results showed that, compared with Comparative Example 1, the band gaps of the nanomaterial samples provided in Examples 1 and 2 were significantly increased.
[0076] exist Figure 4 In the normalized fluorescence spectrum, it can be observed that the fluorescence intensity of the untreated ZnO film in Comparative Example 1 is the highest, followed by the supercritical treated film (Example 1), and the supercritical water treated film is the lowest (Example 2), indicating that supercritical carbon dioxide water modification of ZnO is effective.
[0077] Experimental Example 3
[0078] AFM tests were performed on the supercritical ZnO nanomaterials of Comparative Example 1 and Examples 1-2. The obtained AFM images are shown below. Figures 5-7 As shown.
[0079] like Figure 5 For example, the AFM image of Comparative Example 1, such as Figure 6 The AFM image of Example 1 is shown below. Figure 7 The AFM images for Example 2 show that the film thickness of Comparative Example 1 is 65.929 nm, and the surface roughness is 1.36 nm; the film thickness of Example 1 is 58.816 nm, and the surface roughness is 1.35 nm; while the film thickness of Example 2 is 59.177 nm, and the surface roughness is 1.31 nm. These data indicate that the roughness variations of the films are within a small range, suggesting that the processing method has little impact on the film roughness. Supercritical carbon dioxide treatment did not increase its roughness, thus avoiding large leakage currents and ensuring the subsequent film forming quality.
[0080] Test Example 4
[0081] The electrical properties of the supercritically treated ZnO nanomaterials of Comparative Example 1 and Examples 1-2 were tested using C-AFM. The obtained C-AFM images are shown below. Figures 8-10 As shown.
[0082] like Figure 8 For example, the C-AFM image of Comparative Example 1 is shown below. Figure 9 The C-AFM image of Example 1 is shown below. Figure 10 The image shown is a C-AFM image from Example 2. The results indicate that the impedance of the device was improved after treatment with Example 1 (supercritical) and Example 2 (supercritical water), with the impedance improvement being the most significant after treatment with supercritical water.
[0083] Experimental Example 5
[0084] XPS tests were performed on the supercritical ZnO nanomaterials of Comparative Example 1 and Examples 1-2, and the obtained XPS spectra are as follows: Figures 11-13 As shown.
[0085] The O1s core energy level spectrum of the 1 nm comparative sample clearly shows that the O1s peak of standard ZnO is fitted with three peaks centered at 529.9±0.1 eV, 531.1±0.1 eV, and 532.6±0.1 eV. Based on the binding energy from low to high, these peaks can be divided into lattice oxygen (O2) and lattice oxygen (O2). M ), oxygen vacancy (O V ) and hydroxyl oxygen (O H Compared to Comparative Example 1 (untreated), the oxygen vacancy content in Example 2 (supercritical carbon dioxide water treatment) decreased from 59.86% to 36.86%. It is speculated that supercritical carbon dioxide can entrain water molecules into the thin film, and the hydroxyl groups in the water may fill oxygen vacancies on the zinc oxide surface, thereby improving device performance. This result is consistent with... Figures 11-13 The decrease in steady-state fluorescence of the ZnO thin film is consistent with the phase.
[0086] Experimental Example 6
[0087] The electronic structures of the supercritically treated ZnO nanomaterials in Comparative Example 1 and Examples 1-2 were subjected to UPS testing, and the resulting UPS spectra are shown below. Figures 14-15 As shown.
[0088] Figure 14 The UPS spectra of the nanomaterial samples provided in Examples 1-2 and Comparative Example 1 of this invention at 19.0–16.0 eV (secondary electron cutoff edge); Figure 15 The UPS spectra (Fermi level edge) of the nanomaterial samples provided in Examples 1-2 and Comparative Example 1 of this invention are shown. The spectra results indicate that after supercritical treatment, the downward shift of the conduction band position may increase electron injection, while the downward shift of the valence band position effectively blocks holes from leaking from the quantum dot layer to the electron transport layer, thereby increasing quantum dot radiative recombination.
[0089] Experimental Example 7
[0090] JV characteristics were tested on single-type charge carrier devices of ZnO nanomaterials treated with supercritical fluidization in Comparative Example 1 and Examples 1-2. The obtained JV characteristic curves are shown below. Figure 16 As shown.
[0091] According to the Mott-Gurney equation, under the same applied voltage, mobility is directly proportional to current density. The materials from Examples 1-2 and Comparative Example 1 of this invention were used to fabricate single-carrier (electron) devices. The device structure adopted was: ITO / ZnO (supercritical / supercritical water) / QDs / ZnO (supercritical / supercritical water) / Al. Figure 16 It is evident that the current density of single-electron devices treated with supercritical and supercritical water is lower than that of standard ZnO, and the current of devices treated with supercritical water is lower than that treated with supercritical water. This suggests that supercritical and supercritical water may modify ZnO, thereby suppressing electron transport capacity, reducing Auger recombination, and improving the efficiency roll-off problem.
[0092] Experimental Example 8
[0093] To further investigate whether supercritical carbon dioxide can penetrate the ZnO layer and thus affect the quantum dot layer, we explored the fluorescence quenching of QD by ZnO surface defect states before and after supercritical and supercritical water treatment. Four sets of thin films were prepared. The first set involved spin-coating quantum dots onto a glass substrate and then annealing it directly at 60°C for 30 min. The second set involved spin-coating quantum dots and zinc oxide sequentially onto a cleaned glass substrate and then annealing it directly at 60°C for 30 min. The third set involved spin-coating quantum dots and zinc oxide sequentially onto a glass substrate and then annealing it at 60°C for 30 min. After cooling, the film was treated in a supercritical fluid reaction system at 1200 psi and 50°C for 50 min. The fourth set involved spin-coating quantum dots and zinc oxide sequentially onto a glass substrate and then annealing it at 60°C for 30 min. After cooling to room temperature, the film was placed in a supercritical fluid reaction vessel, 400 μL of ultrapure water was added, and the pressure was set to 1200 psi and the temperature to 50°C for 50 min. The obtained fluorescence spectra are shown below. Figure 17 , Figure 18 As shown in Table 1; among which, Figure 17 For steady-state fluorescence spectra, Figure 18 This is a transient fluorescence spectrum.
[0094] Table 1
[0095] Group τ1(ns) B1(%) τ2(ns) B2(%) τave(ns) QD 2.01 2.68 8.33 97.32 8.16 QD / ZnO 2.08 12.32 5.71 87.68 5.26 QD / ZnO supercritical 2.26 12.01 5.70 87.99 5.28 QD / ZnO supercritical water 2.22 14.40 5.81 85.60 5.29
[0096] Figure 17 The steady-state fluorescence test results show that the fluorescence intensity of QD / ZnO, QD / ZnO supercritical, and QD / ZnO supercritical water treatment remained essentially unchanged. Figure 18The transient fluorescence spectra are presented, and the fluorescence lifetime was fitted using a double exponential method. As shown in Table 1, the lifetimes of the above sample groups did not change significantly, and the steady-state fluorescence test results were similar. This suggests that the influence of supercritical water did not diffuse to the interface layer between QDs and ZnO, or its influence was minimal.
[0097] Experimental Example 9
[0098] The supercritical QLED devices of Comparative Example 1 and Examples 1-2 were subjected to current density-voltage-brightness tests, and the obtained current density-voltage-brightness curves are shown below. Figure 19 As shown.
[0099] The curves clearly show that the leakage current of devices treated with supercritical water in the low-voltage region is significantly lower than that of devices without water and those using standard ZnO as the electron transport layer. Referring to the XPS and AFM test results above, this can be explained by the fact that supercritical treatment reduces the defect states of ZnO and improves the film roughness, thereby reducing leakage current and improving QLED device performance.
[0100] Experimental Example 10
[0101] The supercritical QLED devices of Comparative Example 1 and Examples 1-2 were subjected to luminance-external quantum efficiency tests, and the obtained luminance-external quantum efficiency curves are shown below. Figure 20 As shown in Figure 1 and Table 2.
[0102] Table 2
[0103] Group <![CDATA[L Max (cd / m 2 )]]> <![CDATA[EQE Max (%)]]> Comparative Example 1 206400 12.05 Example 1 130600 11.86 Example 2 115600 12.01
[0104] Depend on Figure 20 The experimental data shows that the external quantum efficiency of the QLED devices in Example 2 is significantly improved. This indicates that the performance is maximized when the devices undergo supercritical treatment and 400 μL of water is added. Referring to the UPS, single-carrier device tests, and C-AFM test results above, it is shown that the ZnO treated in Example 2 has a slightly larger bandgap and a lower conduction band position compared to standard ZnO, resulting in reduced carrier mobility and thus weakening its electron transport capability to some extent. This makes the carrier injection in the device more balanced. Simultaneously, supercritical treatment can compensate for surface defect states in ZnO, thereby effectively reducing the fluorescence quenching of QDs by ZnO. This is because, within an appropriate pressure range, supercritical carbon dioxide can more effectively carry water molecules to the zinc oxide surface, thereby passivating some surface defects and improving device performance.
[0105] It can be seen from the test data in Table 2 that when the supercritical carbon dioxide water treatment affects the quantum dot layer, the brightness of the device will be greatly reduced. However, compared with the standard device, the brightness of the device treated by the supercritical carbon dioxide water in this invention has no obvious change. Therefore, it is speculated that the supercritical carbon dioxide water does not affect the quantum dot layer or has little impact on it.
[0106] Test Example 11
[0107] The QLED devices treated by supercritical treatment in Comparative Example 1 and Examples 1-2 were subjected to a lifetime efficiency decay test, and the obtained lifetime decay curves are as Figure 21 shown.
[0108] In the constant current mode with similar initial brightness maintained, according to the lifetime calculation formula L0 n ×T 50 =K (where K is a constant, 1 < n < 2), assuming the acceleration coefficient n = 1.5, the devices were all converted to an initial brightness of 100 cd / m 2 , the ambient temperature was 15 °C, and the humidity was 25%. The T 95 and T 50 lifetimes of the devices without supercritical treatment were 124 h and 13548 h respectively. Among them, the device of Example 2 (supercritical water treatment) had the longest lifetime, and its T 95 and T 50 lifetimes were 687 h and 18918 h respectively. Followed by that of Example 1 (supercritical treatment), its T 95 and T 50 were 139 h and 14489 h respectively. The experimental results show that the lifetimes of the devices after supercritical and supercritical water treatment have been improved. It can be seen from this that compared with Comparative Example 1 (standard ZnO), the lifetime of the device based on the supercritical-treated ZnO electron transport layer has been improved, which may be attributed to the reduction of the current in the device after supercritical and supercritical water treatment, and the reduction of the heat generated when the device works. The low heat will increase the stability of the device.
[0109] The above are only the preferred embodiments of the present invention, and are not limited to the above examples. For those skilled in the art, various changes and modifications can be made under the principle of the present invention. Any modifications, improvements, etc. should be regarded as within the protection scope of the present invention.
Claims
1. A method for optimizing QLED device performance, characterized in that: The method comprises the following steps: placing the packaged QLED device in a supercritical reactor, introducing carbon dioxide into the reactor, controlling the pressure and temperature in the reactor, and performing supercritical treatment; Alternatively, the packaged QLED device is placed in a supercritical reactor, water is added into the reactor, and then carbon dioxide is introduced into the reactor, and the pressure and temperature in the reactor are controlled to perform supercritical treatment.
2. A method for optimizing QLED device performance according to claim 1, characterized in that: The temperature is 40° C. to 70° C., the pressure is 1000 psi to 1600 psi, and the supercritical treatment time is 20 min to 60 min.
3. The method for optimizing QLED device performance according to claim 1, characterized in that: The temperature is 50° C. to 60° C., the pressure is 1300 psi to 1500 psi, and the supercritical treatment time is 40 min to 50 min.
4. The method for optimizing QLED device performance according to claim 1, characterized in that: The amount of water added is 200-600 μL.
5. The method for optimizing QLED device performance according to claim 1, characterized in that: The amount of water added is 300-600 μL.
6. The method for optimizing QLED device performance according to claim 1, characterized in that: After the supercritical treatment is completed, the carbon dioxide in the reactor is restored to a gaseous state by gradually cooling and releasing the pressure, and the treated QLED device is taken out.
7. The method for optimizing QLED device performance according to claim 1, characterized in that: The QLED device comprises, from bottom to top, anode / hole injection layer / hole transport layer / light-emitting layer / electron transport layer / cathode; the electron transport layer is a ZnO nanomaterial.
Citation Information
Patent Citations
Light-emitting diode supercritical processing method
CN113437187A